1993
DOI: 10.1021/j100132a044
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for determining size distributions in polydisperse micelle systems based on the recovery of fluorescence lifetime distributions

Abstract: A method based on fluorescence lifetime distribution analysis is proposed for the determination of micellar size distributions in polydisperse systems. The exponential series method is employed to determine the lifetime distribution for a probe in the presence of quencher. This distribution is then analyzed by the maximum entropy method in order to recover the size distribution function. The method has been tested on sodium dodecyl sulfate and cetyltrimethylammonium chloride micellar systems in the presence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 15 publications
0
55
2
Order By: Relevance
“…54,59 However, the swollen micelles present at high SDS concentrations have been reported to be polydisperse in size, which indicates a rather small free energy difference between the aggregate sizes. 5,60 We are, however, restricted by the simulation description: Once formed, the micelles are in a local energy minimum, and if the minimum is deep enough, it is unlikely that we see further size evolution within the submicrosecond time window we are able to examine. We conclude that observed micelle sizes provide a lower limit to the actual micelle sizes in the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…54,59 However, the swollen micelles present at high SDS concentrations have been reported to be polydisperse in size, which indicates a rather small free energy difference between the aggregate sizes. 5,60 We are, however, restricted by the simulation description: Once formed, the micelles are in a local energy minimum, and if the minimum is deep enough, it is unlikely that we see further size evolution within the submicrosecond time window we are able to examine. We conclude that observed micelle sizes provide a lower limit to the actual micelle sizes in the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…62,78,79 These differences are important since it has been shown that variations in these experimental conditions can dramatically alter the size and shape of micelles. [80][81][82][83][84][85][86] Therefore, partition coefficients measured in surfactant solutions with additives, under saturated conditions, or at high surfactant concentrations are not necessarily comparable to those measured in systems in which there are no additives and solute and surfactant concentrations are kept low. 72,[87][88][89][90][91] We believe that in order to evaluate the specific chemical interactions which govern the partitioning of solutes in such systems, it is necessary to establish a set of partition coefficients in dilute surfactant systems without any additives present and where the solute concentrations are as low as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Polydispersity in micelle size would give rise to a distribution in k q values and possibly in k 0 as well [33]. Two methods are available that derive average properties of polydisperse micelles from TRFQ data [33,34]. In this work we adopt a combination of a lifetime distribution analysis and the method of Almgren and Lofroth [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Two methods are available that derive average properties of polydisperse micelles from TRFQ data [33,34]. In this work we adopt a combination of a lifetime distribution analysis and the method of Almgren and Lofroth [33,34]. The Infelta model is used as a first approximation to fit the decay data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation